Green spectrofluorimetric method for quantification of sodium oxybate in pharmaceutical and plasma samples - Reem M. Alnemari; Farooq M. Almutairi; Muneef M. Aldhafeeri; Maram H. Abduljabbar; Rami M. Alzhrani; Yusuf S. Althobaiti; Musaad M. Althobaiti; Sherif Ramzy; Atiah H. Almalki (Scientific Reports)
Abstract Sodium oxybate is a newly approved oral treatment for narcolepsy-related cataplexy and excessive daytime sleepiness. It has been misused recreationally and implicated in drug-facilitated crimes. In this study, a highly sensitive and environmentally benign quenching spectrofluorimetric method was established for the quantification of sodium oxybate in both pharmaceutical and spiked plasma matrices. Carbon quantum dots were used as a sustainable fluorescent probe to quantify sodium oxybate via fluorescence quenching. The surface of the fluorescent probe was modified with a sodium oxybate-tetraphenylborate complex to augment selectivity. Sodium oxybate interacts with chromophore sites on the fluorescent probe, leading to a concentration-dependent reduction in the fluorescence intensity of the probe recorded at 450 nm. The method was validated in accordance with the ICH guidelines and demonstrated a good linearity within a working range of 50–600 ng/mL. The method was shown to be sensitive, with detection and quantitation limits of 14.58 and 44.18 ng/mL, respectively. This method was successfully used to quantify sodium oxybate in pharmaceutical and spiked plasma samples, with no interference. Furthermore, the environmental sustainability of the proposed method was evaluated utilizing the Analytical GREEnness calculator metric, yielding a notably elevated greenness score.